A Cooperative Network Monitoring Overlay - Castro, Vasco (2011)
This paper proposes a ﬂexible network monitoring overlay which resorts to cooperative interaction among measurement points to monitor the quality of network services. The proposed overlay model, which relies on the deﬁnition of representative measurement points, the avoidance of measurement redundancy and a simple measurement methodology as main design goals, is able to articulate intra- and inter-area measurements efﬁciently. The distributed nature of measurement control and data confers to the model the required autonomy, robustness and adaptiveness to accommodate network topology evolution, routing changes or nodes failure. In addition to these characteristics, the avoidance of explicit addressing and routing at the overlay level, and the low-overhead associated with the measurement process constitute a step forward for deploying large scale monitoring solutions. A JAVA prototype was also implemented to test the conceptual model design.